2022
DOI: 10.1007/s40264-022-01180-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Reports on Adverse Drug Reactions Related to Herbal Medicinal Products and Herbal Supplements in the Netherlands Received by the National Pharmacovigilance Centre Lareb

Abstract: IntroductionThe inclusion of herbal medicinal products and herbal supplements in pharmacovigilance systems is important because a systematic approach of collecting and analyzing adverse drug reactions related to these products will help practitioners, patients, and regulators to gain more knowledge and prevent harm. Objective We aimed to categorize the adverse drug reaction reports on herbal medicinal products and herbal supplements submitted to the Pharmacovigilance Centre Lareb between 1991 and February 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, it is worth noting that these teas may also present health hazards. Studies have shown that drinking green tea might cause liver damage [ 54 ], and nutritional supplements mixed with herbal ingredients might also cause kidney toxicity or other adverse drug reactions [ 55 ]. Therefore, before taking herbal supplements and tea products, the possible health hazards should be fully evaluated, especially in vulnerable groups such as pregnant women, the elderly, and children.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that these teas may also present health hazards. Studies have shown that drinking green tea might cause liver damage [ 54 ], and nutritional supplements mixed with herbal ingredients might also cause kidney toxicity or other adverse drug reactions [ 55 ]. Therefore, before taking herbal supplements and tea products, the possible health hazards should be fully evaluated, especially in vulnerable groups such as pregnant women, the elderly, and children.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the assumptions that herbal medicinal products are more frequently used by women, and that women are more apt to report an ADR than men (Stjernberg et al, 2006; Zhang et al, 2015). Moreover, women may be more likely to experience side effects than men, since the dosage in relation to their body weight is relatively higher (Van Hunsel, Van der Kooi, et al, 2022). Noteworthy in the age distribution of ADRs, is that the age group of 2–11 years has a large share for both single and multiple ingredient tea tree oil products.…”
Section: Discussionmentioning
confidence: 99%